Bioassay complexities—exploring challenges in aquatic chemosensory research - Hardege, Jorg D.; Fletcher, Nichola; Burnett, Jonathan W.; Ohnstad, Hannah; Bartels-Hardege, Helga D. (Frontiers in Ecology and Evolution, 2024)
Chemosensory science, the study of how organisms produce and assess olfactory information is central to our understanding of how organisms interact and gain information about their environment. Signalling cue identification in aquatic systems lags behindlags our knowledge in terrestrial insects due to analytical challenges in aqueous environments. Unambiguous, reliablereliable, and fast behavioural assays to evaluate the biological activity and function of a chemosensory cue are critical to understand aquatic signalling systems and enable research into their ecology, evolution, and threats in a changing environment. Yet, a range of anthropomorphic assumptions made in this research field create additional challenges to interpret data accumulatedgenerated. Here we evaluate common challenges including assumed readiness of individuals to respond, lack of information on the animals' physiological and social status, their pre-experimental cue exposure, the innate or learned character of the responses, the animals' acclimation and habituation status, and the impact of the animals upon their own environment. These factors lead to significant variability in animals' responses in bioassays, both in the field and in laboratory setups. In the light of our limited knowledge of aquatic chemosensory cues' chemical structure, active concentrations in samples, and undetermined response thresholds, we evaluate methods of mitigation to minimise differences between studies. We conclude that currently it is nearly impossible to compare results from chemosensory behavioural studies undertaken in different ecosystems, laboratories, and